The Effectiveness of Group Counseling Using Role Playing and Behavioral Rehearsal Techniques to Reduce Students’ Aggressive Behavior - Wathaniyah, Nurul; Japar, Muhammad; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Aggressive behavior is a common problem found in students. Thus, the present study strived for examining the effectiveness of group counseling with role playing and behavioral rehearsal techniques to reduce students’ aggressive behavior. It used randomized pretest-posttest comparison group design and involved 21 students divided into three groups. Those who participated in this study were the ones with high level of aggressive behavior. To collect the behavioral data, the researchers used Aggression Questionnaire scale that has been adapted to Indonesian and obtained alpha coefficient of 0.75. Based on Wilcoxon test, the group counseling which separately applied role playing, and behavioral rehearsal technique has effectively reduced aggressive behavior. Even, when those techniques were combined better results were obtained. These prove that this intervention can be implemented as an effort to reduce students’ aggressive behavior.